Multifunctional molecular hybrid for targeted colorectal cancer cells: Integrating doxorubicin, AS1411 aptamer, and T9/U4 ASO - Kanpitcha Jiramitmongkon; Pichayanoot Rotkrua; Paisan Khanchaitit; Jiraporn Arunpanichlert; Boonchoy Soontornworajit (PLoS ONE, 2025)
Colorectal cancer (CRC) poses a global health challenge, with current treatments often harming both cancerous and normal cells. To improve efficacy, a multifunctional drug delivery platform has been developed, integrating bioactive materials, anticancer agents, and targeted recognition ligands into a single molecule. This study aimed to create a molecular hybrid (MH) containing doxorubicin, AS1411 aptamer, and T9/U4 ASO to regulate SW480 cell proliferation. The AS1411 aptamer targets nucleolin, overexpressed on cancer cell membranes, while T9/U4 ASO inhibits human telomerase RNA activity, further hindering cancer cell proliferation. AS-T9/U4_MH was synthesized via oligonucleotide hybridization, followed by doxorubicin loading and evaluation of its impact on cell proliferation. Binding capability of this MH was verified using fluorescence microscopy and flow cytometry, demonstrating specific recognition of SW480 cells due to nucleolin availability on the cell surface. These findings were corroborated by both microscopy and flow cytometry. AS-T9/U4_MH exhibited anti-proliferative effects, with the doxorubicin-loaded system demonstrating encapsulation and reduced toxicity. Moreover, the presence of Dox within AS-T9/U4_MH led to a notable reduction in hTERT and vimentin expression in SW480 cells. Additionally, examination of apoptotic pathways unveiled a marked decrease in Bcl-2 expression and a simultaneous increase in Bax expression in SW480 cells treated with Dox-loaded AS-T9/U4_MH, indicating its impact on promoting apoptosis. This molecular hybrid shows promise as a platform for integrating chemotherapeutic drugs with bioactive materials for cancer therapy.